The lesser two-horned rhinoceros - Mohd. Momin Khan 1935- (Big 5 Malaysian animal series, 2014)
Traditional Chinese medicine utilises Rhino horn and most other parts of its body. The species has been hunted for more than a thousand years and there seems to be no place that is safe for the rhino. Poachers are not local but come from Thailand, Cambodia and Vietnam. They virtually live in our forest and are quite fearless of the authorities. The species is critically endangered and need the greatest care and protection. The world population is approximately one hundred Rhinos. Captive breeding has achieved success and offers some hope of saving the species.